Tracking Benefits of Janani Suraksha Yojana—A Maternal Cash Transfer Scheme: Evidence from Rajasthan, India. (June 2014) - Purohit, Neetu; Mehra, Vrinda; Govil, Dipti
Janani Suraksha Yojana (JSY) is more often than not recognized only as a cash transfer scheme for institutional deliveries. Since its pan India introduction in 2005, the scheme has passed through various stages which affected its implementation in multiple ways. The scheme, however, could not earn the reputation of an intervention which affected maternal health in any phenomenal way other than increasing institutional deliveries. After five years of its implementation, the present paper attempts to highlight the areas where JSY has positively contributed; if not directly, indirectly in affecting maternal health and the psyche of the community. The article provides evidence from primary data collected from 424 women who delivered during April 2010–March 2011 in selected villages of four districts of Rajasthan, India. Findings from other population-based studies conducted in the state of Rajasthan since the launch of JSY have also been considered to support the findings of the current study presented in the paper. It attempts to show that though JSY incentives were contingent on institutional delivery alone; it led to improvement of other services which have positively affected maternal and child health in terms of health seeking behaviour of the community. Chi square test was employed and it shows health behaviour of those who availed JSY benefits to be significantly associated with registration of pregnancy (p < 0.01), antenatal checkups (p < 0.05), duration of stay at the institution post-delivery (p < 0.01), initiation of breastfeeding (p < 0.5) and postnatal checkup (p < 0.01).